The influence of outdoor play spaces in urban parks on children's social anxiety - Bao, Yu; Gao, Ming; Luo, Dan; Zhou, Xudan (Frontiers in Public Health, 2022)
Urban green spaces are critical to the healthy development of children's social interactions and activities. However, the relationship between urban green spaces for children's activities and the alleviation of children's social anxiety remains unclear. In this study, we aimed to explore the link between spatial characteristics and social anxiety in children. To explore the coupling relationships among green space, play space, and social anxiety, an assessment of children's play spaces and levels of social anxiety was performed using self-reported data, OpenStreetMap captured the characteristic indicators of urban parks, and the ArcGIS and SPSS softwares were used for the mathematical analysis. The results showed that (1) both the NDVI and 10-min accessibility were significantly negatively related to children's social anxiety; (2) the diversity of service facilities, surfacing materials, and the attractiveness and challenge of the environment were negatively related to children's social anxiety; (3) there were significant differences between activity types and social anxiety. These results provide design references and a theoretical basis for improving the benefits of urban green space on children's health and wellbeing.